2019
DOI: 10.3390/molecules24030621
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of 177Lu-PSMA-617 after Mannitol Infusion and Glutamate Tablet Administration: Preliminary Results of EUDRACT/RSO 2016-002732-32 IRST Protocol

Abstract: Radio-ligand therapy (RLT) with177Lu-PSMA-617 is a promising option for patients with metastatic castration-resistant prostate-cancer (mCRPC). A prospective phase-II study (EUDRACT/RSO,2016-002732-32) on mCRPC is ongoing at IRST (Meldola, Italy). A total of 9 patients (median age: 68 y, range: 53–85) were enrolled for dosimetry evaluation of parotid glands (PGs), kidneys, red marrow (RM) and whole body (WB). Folic polyglutamate tablets were orally administered as PGs protectors and 500 mL of a 10% mannitol sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Polyglutamate tablets were orally administered as a substrate for PSMA receptors, and external ice packs were applied to the neck region (3). The dosimetry evaluation performed on 13 patients showed a lower absorbed dose in both parotid and submandibular glands compared with previously published data (11,12). The efficacy results of the protectors proposed in our study, especially for salivary glands, were encouraging in the context of TAT, as they could potentially improve treatment management, enabling wider use of this therapeutic approach.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Polyglutamate tablets were orally administered as a substrate for PSMA receptors, and external ice packs were applied to the neck region (3). The dosimetry evaluation performed on 13 patients showed a lower absorbed dose in both parotid and submandibular glands compared with previously published data (11,12). The efficacy results of the protectors proposed in our study, especially for salivary glands, were encouraging in the context of TAT, as they could potentially improve treatment management, enabling wider use of this therapeutic approach.…”
Section: Introductionsupporting
confidence: 56%
“…The salivary gland dose value was calculated as the mean between PG and SG dose values for each patient. More details are reported in Sarnelli et al (11). Although the focus of the present study is salivary glands, for the sake of completeness, we reported the predicted dose also for the other considered organs.…”
Section: Dosimetrymentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the increased risk of chronic renal disease prevents initiation of PSMA-RLT earlier in disease course (14). Many attempts including sialendoscopy with dilatation, saline irrigation, steroid injection, intraparenchymal injections of botulinum toxin, external cooling of the salivary glands with ice-packs and oral administration of folic polyglutamate tablets have been tried to mitigate salivary gland toxicity with some, but limited success (15)(16)(17)(18). Mannitol infusion is a strategy to reduce renal uptake of PSMA-targeted tracers by acting as an osmotic diuretic, decreasing renal reabsorption.…”
Section: Introductionmentioning
confidence: 99%